Towards Sustainable Innovations - essay in memoriam of Andries Nentjes - Yoram Krozer (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This paper assesses theoretically and empirically three key factors for sustainable development within context of debates about economy and environment: autonomous technological change, induced technological change and barriers of entry to innovations. ~ Design/research methods: The paper covers a literature review on strong versus weak sustainability, followed by an explanation of autonomous technological change. Statistical analysis with literature review on induced technological change due to consumers' and policy demands for sustainable innovations, as well as literature review on policy support for the incumbent interests that rival sustainable innovations is provided. The information used is largely based on two chapters in the book on sustainable innovations (Krozer 2015), and presented in the context of long scientific cooperation with the late Andries Nentjes. ~ Conclusion/findings: The economic theoretical debates are hardly relevant for policies on sustainable innovations, because political views are inconsistent with observations and change during fluctuations in economic outcomes. The main conclusion is that autonomous technological change is the driver of sustainable innovations. Present policies pose barriers of entry to sustainable innovations, where the global value of support for vested interest exceeds the market potential for induced technological change due to demands of policies and consumers put together. ~ Originality/value of the paper: The study contribution to understanding of autonomous and induced technological change, showing that shifting policy support away from the incumbent interests towards sustainable innovations is key for sustainable development.
Keywords: 330; sustainable innovations; income; environment; consumers; business support